Development of media compositions of Lactobacillus plantarum for improvement of scavenging ability of Curcuma caesia - Jemain, Siti Fathimah Putery; Parveen, Jamal; Jaswir, Irwandi; Amid, Azura; Raus, Raha Bt. Ahmad (Malaysian Society of Applied Biology, 2019)
This study focuses on increasing DPPH scavenging ability of C. caesia crude extract by incorporating it into the growth media of Lactobacillus plantarum after screening and optimizing selected growth factors of the media through Plackett Burman experimental design and face centered central composite design (FCCCD).